Italy : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Italy. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that the Italian economy is in the third year of a moderate recovery. Supported by exceptionally accommodative monetary policy, fiscal easing, low commodity prices, and the government's reform efforts, the economy grew by 0.9 percent in 2016 and continued to expand in the first quarter of 2017. Unemployment and nonperforming loans have declined somewhat from their crisis-driven peaks. Growth is projected at about 1.3 percent in 2017 and about 1 percent in 2018-20 as favorable tailwinds become less supportive. Growth could surprise on the upside in the near term, including from a stronger European recovery.